Development of Cattle Disease Diagnosis Expert System (CaDDES): A web application for the diagnosis of cattle diseases - KRISHNAMOORTHY, P; DHARSHAN, H V; CHANDRASEKHAR, T M; SURESH, K P (The Indian Journal of Animal Sciences, 2023)
In the present study, an attempt was made to develop an expert system for the diagnosis of cattle diseases under field conditions by Veterinarians. A questionnaire tool was developed and used for collecting the scores for symptoms or signs of 13 cattle diseases for diagnosis. The tool was tested for face validity by pilot survey with experts and content validity by calculating Aiken’s value index. The scores for the signs or symptoms were collected from 178 field veterinarians from different states in India. The scores obtained were tested for reliability and consistency by using the split-half test [88.7%] and Cronbach’s alpha coefficient [92.7%], respectively. The weighted matrix was calculated for the 51 signs or symptoms obtained for 13 cattle diseases. The CaDDES, a web application wasdeveloped using PHP, HTML, JavaScript, and MySQL computer programming languages. This web application contains Home, Introduction, About CaDDES, Disease Diagnosis, Development Team, and Contact pages. The Veterinarians need to enter the basic details of cattle and select the signs or symptoms observed in the particular cattle under field conditions. The results page will display the three probable diseases diagnosed for the selected signs or symptoms. Further, the necessary samples to be collected for laboratory confirmation and preventive measures to be undertaken were also provided. This web application will be useful for field level diagnosis of cattle diseases by Veterinarians and later by farmers. It may also be useful as a surveillance application, which will improve cattle disease reporting in the future.